THE EFFECTIVENESS OF KETOGENIC DIET IN TREATMENT OF EPILEPSY PATIENTS: A LITERATURE REVIEW - Arif Hidayatullah; I Made Kariasa (International Journal of Nursing and Health Services (IJNHS), 2019)
The ketogenic diet is one of the alternative treatment management of epilepsy patients. The study aimed to examine the effect of the ketogenic diet for managing the epilepsy patients. A literature review used by databases to find the relevant articles included Science Direct, Scopus, and Pro-Quest from 2011 to 2018. Metabolic therapy with the ketogenic diet can improve mitochondrial function, increase inhibition, and reduce nerve stimulation, which can cause seizures in epilepsy patients. Also, other factors need to be considered to produce an optimal impact on the use of the ketogenic diet, such as patient compliance and age. The ketogenic diet is one of the non-pharmacological alternatives that can be done to prevent recurrence in epilepsy patients. Keywords: ketogenic diet, epilepsy, literature review